A rare occurrence of spindle cell tumor (smooth muscle origin) in a pediatric mandible positive to tumor marker Ki67 causing a therapeutic dilemma - Yogesh Kini; Charu Girotra; Darshi Jain; Komal Navalkha; Damini Gupta (Elsevier, 2022)
A rare case of spindle cell tumor of low histologic grade, smooth muscle origin in mandible of 11 year old girl is reported together with the conventional histologic and immunohistochemical findings. The tumor was in left retromolar region showing rapid increase in size and clinical features suggestive of malignancy. However on histopathologic evaluation it was diagnosed as Benign Spindle Cell tumor of possibly smooth muscle or fibroblastic origin. On Immunohistochemical evaluation the tumor cells were positive for Desmin, Smooth muscle actin but negative for S100. The Ki67 labelling index was 10-15%.The diagnosis was supported by the mitotic rate and Ki67.